HISTOPATHOLOGICAL CHANGES IN ADULT MALE RAT’S LIVER INDUCED BY CONTINUOUS DARKNESS (Iraqi Journal of Medical Sciences, 2016)
Background:It is well known that liver is an endocrine as well as exocrine gland; it also synthesizes, accumulates, detoxifies and transports certain substances. Melatonin is the principle hormone of the pineal gland, which is mainly secreted at night and it is definitely documented to regulate the physiology of all tissues and cells keeping their normality.Objective:This work is designed to study the effect of continuous darkness on hepatic tissues.Methods:Adult Wister albino rats were kept in complete 24 hours darkness for successive 4 periods. Rats were divided into 16 groups. Group II, III, IV and V were left in continuous darkness for 2, 4, 6 and 8 weeks, respectively. Group I†, Group I††, Group I†††, and Group I†††† were the control groups for group II, III, IV and V correspondingly. After the last day of the dark period for each group, the animals were dissected under effect of anesthesia. The liver was weighed and right lobe of liver was processed for study its histopathology.Results:The results showed no important histopathological effect on short and medium periods, while on long periods; there was histopathological changes represented by clear lobulation and inflammatory cell infiltrations.Conclusion:Continuous darkness affects the hepatic tissues of rats depending on the length of exposure.Key words: Melatonin, Darkness, Liver injury.
Keywords: Melatonin; Darkness; Liver injury